Rib Fractures and Mortality: Breaking the Causal Relationship. Issue 11 (November 2019) - Bankhead-Kendall, Brittany; Radpour, Sepeadeh; Luftman, Kevin; Guerra, Erin; Ali, Sadia; Getto, Christopher; Brown, Carlos V.R.
Rib fractures have long been considered as a major contributor to mortality in the blunt trauma patient. We hypothesized that rib fractures can be an excellent predictor of mortality, but rarely contribute to cause death. We performed a retrospective study (2008–2015) of blunt trauma patients admitted to our urban, Level I trauma center with one or more rib fractures. Medical records were reviewed in detail. Rib fracture deaths were those from any respiratory sequelae or hemorrhage from rib fractures. There were 4413 blunt trauma patients who sustained one or more rib fractures and 295 (6.8%) died. Rib fracture patients who died had a mean Injury Severity Score = 38 and chest Abbreviated Injury Score = 3.4. Rib fractures were the cause of death in only 21 patients (0.5%). After excluding patients who were dead on arrival, patients dying as a result of their rib fractures were found to be older ( P < 0.0001) and had a higher admission respiratory rate ( P = 0.02). Multivariable logistic regression found that age ≥65 was the only variable independently associated with mortality directly related to rib fractures (odds ratio 4.1, 95% confidence interval = 1.3–13.3, P value < .0001). Mortality in patients with rib fractures is uncommon (7%), and mortality directly related to rib fractures is rare (0.5%). Older patients are four times more likely to die as a direct result of rib fractures and may require additional resources to avoid mortality.